Is overweight or obesity associated with anemia in children? Follow-up of Samoans in the Ola Tuputupua'e "Growing Up" study. Issue 2 (March 2022) - Choy, Courtney C.; Howe, Chanelle J.; Soti-Ulberg, Christina; Naseri, Take; Reupena, Muagututia S.; Duckham, Rachel L.; Hawley, Nicola L.
Abstract: Objectives: Globally, there is growing evidence of a double burden of malnutrition with obesity coexisting alongside micronutrient deficiencies across the life course. An emergent double burden poses a threat to health during childhood in Samoa: among 2–4-year-olds with overweight/obesity, 42.9% were anemic. Previous research suggests that obesity-related inflammation may increase the risk of iron deficiency or anemia in children. To test this hypothesis, we examined whether overweight/obesity at 2–4 is associated with anemia at 3.8–6 years old among Samoan children. Methods: Data were obtained from the Ola Tuputupua'e "Growing Up" cohort study. Overweight/obesity at 2–4 years old was classified by body mass index-for-age Z-score > +2 SD. Anemia was defined as hemoglobin < 110 g/L for under 5-year-olds and < 115 g/L for 5–6-year-olds. Prevalence ratios (PRs) for anemia at 3.8–6 years old were estimated by fitting modified Poisson regression models. Results: In our sample of 197 children, 16.24% (n = 32) were affected by overweight/obesity at 2–4 years old and 26.90% (n = 53) had anemia at 3.8–6 years old. After covariate adjustment, the prevalence of anemia was 18% lower among children with overweight/obesity at 2–4 years old compared to those without (PR:0.82; 95% CI:0.42–1.63); however, the corresponding confidence interval was imprecise and inclusive of a higher prevalence. Conclusions: There was not strong evidence to support a relationship between overweight/obesity and anemia in Samoan children, suggesting that obesity-related inflammation may not be related to iron deficiency nor anemia in this setting. Further investigation of the antecedents of overweight/obesity and anemia is critical to inform integrated action to improve health in Samoa. Highlights: There is a moderate prevalence of both anemia and obesity among Samoan children aged 2-6 years. No strong evidence to support a relationship between anemia and overweight/obesity. Longitudinal research and interventions for anemia and overweight/obesity are needed.